Dampak Bahasa Gaul Dalam Sosial Media Terhadap Perubahan Pola Penggunaan Bahasa Indonesia Gen Z - Simanjuntak, Timothy Boy Dani; Silalahi, Tiar Arini Adelia; Tamba, Rodimas; Marbun, Gerrard G.S; Brahmana, Daniel Pederico; Nainggolan, Winda Jessica; Pulungan, Hendra Kurnia (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The development of information and communication technology, particularly social media, has brought significant changes in the use of everyday language. Language development today is progressing rapidly alongside the increasing use of social media platforms such as TikTok, Instagram, and WhatsApp. Generation Z, as a generation that has grown up with the advancement of social media, has experienced a shift in language patterns in daily life. Based on this issue, the research raises the following problems: (a) How is slang used by Generation Z on TikTok? (b) How does the use of slang on TikTok influence the changes in Indonesian vocabulary among Generation Z? (c) What is the impact of slang use on TikTok toward the changes in Indonesian grammar among Generation Z? This study employs a descriptive qualitative approach. Data collection methods include observation and literature review. The use of slang by Generation Z shows that social media plays a crucial role in shaping the communication patterns of young people. First, the use of slang on TikTok is not merely a spontaneous expression but also becomes part of Generation Z’s digital identity. Slang appears in the form of abbreviations, acronyms, borrowed foreign terms, and the creation of new vocabulary, all of which function to strengthen the sense of togetherness and solidarity among members of online communities.